Case Report: Tumor-to-tumor metastasis: a rare case of prostate adenocarcinoma metastasis to lung squamous cell carcinoma in a patient with multiple primary malignancies - Pei, Baoxiang; Liu, Jikuan; Hu, Zhiliang; Pan, Fen (Frontiers in Oncology, 2025)
IntroductionTumor-to-tumor metastasis (TTM) is a rare occurrence in patients with two separate primary tumors, with the more malignant tumor more commonly metastasizing to a separate primary benign or low-grade tumor. Lung carcinomas are the most common metastatic tumor donors. However, the opposite phenomenon (lung carcinoma as a recipient of metastasis from prostate adenocarcinoma) is rarely previously reported in the literature. We report the case of TTM from prostate cancer to coexisting primary lung cancer.Case reportThe 69-year-old male patient underwent surgery for tongue cancer on March 16, 2024, during which a lung mass was discovered in the right lower lung. The lung mass increased in size by follow-up thoracic computed tomography scan on October 4, 2024. Subsequently, the patient underwent single-port thoracoscopic right lower lung lobectomy and mediastinal lymph node dissection. Postoperative pathological results revealed that the lung mass had two components: lung squamous cell carcinoma and prostate cell carcinoma. MRI evaluation and PSA tests confirmed a prostate mass on November 8, 2024. Further, ultrasound-guided transperineal prostate biopsy was performed, and the biopsy pathology indicated prostate acinar adenocarcinoma. Subsequently, the patient underwent robot-assisted laparoscopic prostatectomy.ConclusionsThis case report presents a rare and intriguing instance of TTM, specifically describing prostate adenocarcinoma metastasizing to a primary lung squamous cell carcinoma. The manuscript contributes valuable documentation to the limited literature on this rare phenomenon and is of potential interest to the oncology community.